Analisis Metode Proyek Kegiatan 3M (Mewarnai, Menggunting, dan Menempel) dalam Meningkatkan Kemampuan Motorik Halus Anak Usia di TK IT Qur’an - Nur ‘Ilma; Novita Friska; Aminda Tri Handayani; Juli Yanti Harahap (Mataram University, 2026)
Fine motor skills are an essential aspect of early childhood development, as they are closely related to hand-eye coordination, writing readiness, and the ability to perform daily activities. However, in kindergarten learning practices, some children still experience difficulties in controlling finger and hand movements. Therefore, creative and engaging learning methods are needed, one of which is the project-based 3M activity method (coloring, cutting, and pasting). This study aimed to analyze the effectiveness of the 3M project activity method in improving the fine motor skills of early childhood learners at TK IT Qur'an Kisaran. This research employed a qualitative descriptive approach. The research participants consisted of 15 children in Group B of TK IT Qur'an Kisaran, including 7 boys and 8 girls. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the 3M project activity method gradually improved children's fine motor skills. The children became more proficient in holding writing tools, using scissors correctly, and arranging picture patterns through pasting activities. In addition, they demonstrated greater participation, motivation, and enthusiasm during the learning process. It can therefore be concluded that the 3M project activity method is effective in enhancing the fine motor skills of early childhood learners at TK IT Qur'an Kisaran.